THE EFFECTIVENESS OF ROLE PLAY METHOD TOWARD STUDENTS’ MOTIVATION IN ENGLISH CONVERSATION - Samsibar Samsibar; Wahyuddin Naro (Universitas Islam Negeri Alauddin Makassar, 2018)
This study aims to find the effectiveness of role play method toward the students’ motivation in English conversation for the first grade students at MTs As’adiyah No. 49 Bola Aserae – Belawa academic year 2016/2017. The method used in this study was quantitative research through pre-experimental method by using one shot case study pre-test and post-test design. Before the treatment, the reseracher did the pre-test in one class. Moreover, the researcher taught English conversation by role play technique in the experimental class. The last, the researcher conducted the post-test to know whether a role play technique was effective for teaching English conversation in experimental class. As the quantitative method, the researcher analized the data by using the t-test (4.37) which was higher than t-table value (2.093). The result showed that there was significant difference on the students’ speaking achievement taught by using role play. The students’ mean score of the pre-test of the experiment class was 52.4. Then, in the post-test, the mean score of experiment class was 65. Therefore, hypothesis H0 was rejected and H1 was accepted. It could be said that role play method was effective in teaching English conversation toward the students’ motivation for the first grade of junior high school students.